2022
DOI: 10.3390/vetsci9090503
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chicken Respiratory Pathogens in Live Markets of Addis Ababa, Ethiopia, and Epidemiological Implications

Abstract: A moderate to high seroprevalence of exposure to Newcastle disease (NDV), avian metapneumovirus (aMPV), infectious laryngotracheitis virus (ILTV), infectious bronchitis virus (IBV) and Mycoplasma gallisepticum (MG) has recently been reported in Ethiopia, but it is unclear to what extent these contribute to clinical cases of respiratory disease. This study investigated the presence of these pathogens in chickens exhibiting respiratory disease in two live markets in Addis Ababa. Markets were visited weekly for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…21 Likewise, a significant proportion of the virus was detected from collected samples targeting the F gene in a study conducted in two open markets of Addis Ababa in 2022. 22 In two states of India, it was also reported that it was possible to determine the prevalence of the disease by detecting the M gene of the virus. 23,24 In this study, antibody against ND was detected in a higher proportion of the samples (68%) even though the sampled birds were not vaccinated (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…21 Likewise, a significant proportion of the virus was detected from collected samples targeting the F gene in a study conducted in two open markets of Addis Ababa in 2022. 22 In two states of India, it was also reported that it was possible to determine the prevalence of the disease by detecting the M gene of the virus. 23,24 In this study, antibody against ND was detected in a higher proportion of the samples (68%) even though the sampled birds were not vaccinated (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Even short-term stability at a high temperature, such as 37 °C, is considered important for manufacturing, handling, and distribution of vaccines in less developed areas, such as rural locations and home-based producers’ properties. These ones are the main source of poultry production in sub-Saharan countries [ 4 , 5 , 6 ]. Moreover, the functional or infectious titer was stable after storage for 16 weeks at 21.5 °C and after 24 weeks at 4 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Even short-term stability at a high temperature, such as 37 • C, is considered important for manufacturing, handling, and distribution of vaccines in less developed areas, such as rural locations and home-based producers' properties. These ones are the main source of poultry production in sub-Saharan countries [4][5][6]. Moreover, the functional or infectious titer was stable after storage for 16 weeks at 21.5 • C and after 24 weeks at 4 • C. Linear regression analyses of the formulation L2 data indicated that the t1/2 for Ad-CMV-F functional titer loss at 4 • C is 94.7 months, i.e., 7.9 years, a slightly longer half-life than previous findings with the A195 formulation [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were collected and processed for routine Polymerase Chain Reaction (PCR) testing, following the pooling of every 5 samples. The PCR analysis aimed to identify common poultry viruses, including Marek’s disease virus (MDV), avian influenza virus (AIV), infectious bursal disease virus (IBDV), infectious bronchitis virus (IBV), reticuloendotheliosis virus (REV), chicken infectious anemia virus (CIAV) [ 32 , 33 , 34 , 35 ]. Bacterial isolation was also conducted using a Luria–Bertani agar plate, MacConkey agar plate, and Blood agar plate.…”
Section: Methodsmentioning
confidence: 99%